Spastic cocontraction of triceps surae increases with the tension applied during swing phase of gait in chronic hemiparesis - Hutin, Emilie; Ghédira, Mouna; Mardale, Valentina; Loche, Catherine-Marie; Gault-Colas, Caroline; Gracies, Jean-Michel; Bayle, Nicolas (Annals of physical and rehabilitation medicine, 2017)
The present study aimed to quantify the impact of the tension applied on triceps surae during the swing phase of gait on its cocontraction in chronic hemiparesis. Forty-one subjects with chronic hemiparesis (50±15 years; time since lesion, 7±7 years; mean±SD) completed a kinematic gait analysis, barefoot at comfortable speed (10 opto-electronic cameras, 6 dynamometric force plates, 27±13 cycles analyzed/subject), with electromyography of soleus (so) and gastrocnemius medialis (gm) on the paretic side. The Coefficients of Spastic Cocontraction, CSCso and CSCgm, were calculated over 3 periods of swing phase (T1, [0–33] %; T2, [34–66] %; T3, [67–100] %), by the ratio of the RMS of the electromyogram in the period of interest over the RMS of the electromyogram of the same muscle over 100ms around the maximal agonist isometric activity (measured on standing position by a maximal effort against resistance). In addition, a coefficient of lengthening of triceps surae, CLts, was computed over each period in the sagittal plane, from the ankle/knee displacements recorded during the period of interest divided by the total range of ankle/knee movements measured across all gait cycles. CSCso, CSCgm and CLts were compared between the 3 periods (ANOVA, significant effect P<0.05). Exploration of individual correlations were performed with all gait cycles of each patient, using univariate regression analysis with CLts as predictor and coefficients of spastic cocontraction (CSCso and CSCgm) as dependent variables. Between T2 et T3, CSCso increased by 233±54% (mean±SEM, P<1E-5) and CSCgm by 67±10% (P=0.0017). CLts increased by 23±7% in T2 (P=0.009) and 52±12% in T3 (P<1E-5). CLts was positively correlated with CSCso in 63% of cases (n=25, r=0.63±0.04, P<0.1) and with CSCgm in 53% of cases (n=21, r=0.60±0.04, P<0.1). In chronic hemiparesis, tension (lengthening) applied on triceps surae is associated with the increase of its spastic cocontraction during swing phase of gait at comfortable speed.